Numerical investigation of the dynamic responses of steel-concrete girder bridges subjected to moving vehicular loads. (March 2021) - Gao, Qingfei; Zhang, Kun; Wang, Tong; Peng, Weikang; Liu, Chengqing
The steel-concrete composite girder bridge is a new type of bridge. The steel girder and concrete slab are connected together by connectors and bear the common force so that the tensile performance of steel and the compressive performance of concrete can be fully utilized. The advantages are obvious. However, research on the dynamic analysis of steel-concrete composite beam bridges is still relatively rare, and the dynamic effects on these bridges from vehicles are becoming increasingly significant. In this paper, a more complex steel-concrete composite simply supported beam bridge model and the entire vehicle model are established, and five steel-concrete connection levels of the bridge model are considered. Using the finite element model, the effects of five factors, namely, bridge natural frequency, vehicle natural frequency, vehicle speed, vehicle lateral position and bridge deck roughness, on the dynamic load allowance ( DLA ) of the composite girder bridge are studied. The influence of vehicle speed and bridge surface roughness on the DLA has a strong regularity. The change in the DLA of the lateral position of the vehicle is highly symmetrical, and the DLA value at the side beam is larger than that of the center beam. Changes in bridge vibration frequency and vehicle vibration frequency can bring about significant changes in the DLA, and the closer the two frequencies are, the more significant the DLA increases, and the more likely it is to produce resonance.